The world distribution of household wealth - James B. Davies; Susanna Sandström; Anthony Shorrocks; Edward N. Wolff (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
There has been much recent research on the world distribution of income, but also growing recognition of the importance of other contributions to well-being, including those of household wealth. Wealth is important in providing security and opportunity, particularly in poorer countries that lack full social safety nets and adequate facilities for borrowing and lending. We find, however, that it is precisely in the latter countries where household wealth is the lowest, both in absolute and relative terms. Globally, wealth is more concentrated than income both on an individual and national basis. Roughly 30 per cent of world wealth is found in each of North America, Europe, and the rich Asian-Pacific countries. These areas account for virtually all of the world's top 1 per cent of wealth holders. On an official exchange rate basis India accounts for about a quarter of the adults in the bottom three global wealth deciles while China provides about a third of those in the fourth to eighth deciles. If current growth trends continue, India, China and the transition countries will move up in the global distribution, and the lower deciles will be increasingly dominated by countries in Africa, Latin American and poor parts of the Asian-Pacific region. Thus wealth may continue to be lowest in areas where it is needed the most.
Keywords: D31; E01; E21; O10; 330; wealth; net worth; personal assets; wealth inequality; households; balance sheets; portfolios